Smoke signals of Australian aborigines. - Magarey, A. T.; Australasian Association for the Advancement of Science. Meeting 1893 : Adelaide, S.A.) ([Adelaide : The Author, 1893)
Course of procedure; detailed account of methods producing types of smoke used in signalling meanings given by Powells Creek, Barrow Creek, Macdonnel Ranges, Tennants Creek, Moorundie & Port Darwin natives; review of previous literature.
"Read at the Adelaide meeting of the Australasian Association for the Advancement of science, held September, 1893".
Caption title.
With which is bound his Aboriginal water-quest. [Adelaide, 1895].
Keywords: Aboriginal Australians -- Social life and customs; Smoke signals; Ngayawung people (S7) (SA SI54-10); Warumungu people (C18) (NT SE53-10); Communications - Nonverbal - Smoke signals; Larrakia / Laragiya / Gulumirrgin people (N21) (NT SD52-04); Darwin (NT Top End SD52-04); Barrow Creek (Central NT SF53-06); Macdonnell Ranges (South Central NT SF53-13, SF53-14); Moorundie (SE SA SI54-10); Tennant Creek (Central NT SE53-14); Powell Creek (North NT SE53-10)